2021
DOI: 10.4067/s0717-95022021000300858
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of the Anatomical Variations of the Posterolateral Tubercle of Talus

Abstract: The aim of our study was to determine the prevalence and the anatomical variations of the posterolateral tubercle of talus in relation to sex on CT imaging. A total of 1478 ankle CT scans was retrospectively reviewed for the different anatomical variants of the posterolateral tubercle of talus, the type and size of os trigonum. Normal sized lateral tubercle was found in 46.1 %, an enlarged posterolateral tubercle (Stieda's process) in 26.1 %, os trigonum in 20.5 % and almost absent tubercle in 7.3 %. A statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The incidence rates of os trigonum, accessory navicular and os peroneum in our subjects were higher than the rates of 2.3%, 11.7% and 4.7% reported by Coskun et al [9], but lower than the 23.5%, 28.2% and 31.8% reported by Cilli et al [8]. Additionally, in our previous studies, the frequency of occurrence for os trigonum and accessory navicular was considerably higher in comparison with the current study (26.1% and 22.9%, respectively) [19,20]. One of the reasons could be that CT scans were used for os trigonum detection, which have higher sensitivity for detecting accessory ossicles compared to conventional radiographs.…”
Section: Discussioncontrasting
confidence: 71%
“…The incidence rates of os trigonum, accessory navicular and os peroneum in our subjects were higher than the rates of 2.3%, 11.7% and 4.7% reported by Coskun et al [9], but lower than the 23.5%, 28.2% and 31.8% reported by Cilli et al [8]. Additionally, in our previous studies, the frequency of occurrence for os trigonum and accessory navicular was considerably higher in comparison with the current study (26.1% and 22.9%, respectively) [19,20]. One of the reasons could be that CT scans were used for os trigonum detection, which have higher sensitivity for detecting accessory ossicles compared to conventional radiographs.…”
Section: Discussioncontrasting
confidence: 71%
“…Although there are different classifications in the literature, SP and OT are entirely different from each other, and their differentiation is necessary to treat caused disorders properly. Furthermore, a higher prevalence of SP was found in males, while OT was higher in females (Kalbouneh et al 2021). In the study of Zwier et al, the frequency of SP was found in about one-third of the patients without OT, with an incidence of 35.7% in the Netherlands (Zwiers et al 2018).…”
Section: Prevalencementioning
confidence: 89%
“…Little knowledge about the incidence of SP is available in the literature (Kalbouneh et al 2021). It might result from the SP that has not part of a standard definition or classification system (Kalbouneh et al 2021).…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations